ANALISIS KUALITAS SUMBER AIR DI DESA PALAAN KECAMATAN NGAJUM KABUPATEN MALANG - Zainal Abidin; Farahdilla Andhika Y.F; Muhammad Imron; Ma'rifatul Ilma Islamia (Jurnal Environmental Science, 2021)
ABSTRACTThe objectives of this study are: 1) to determine the quality of water sources in Microbiological, Physical, and Chemical terms at Campus 2 Unira Palaan Village, Ngajum District, Malang Regency, 2) determine the feasibility of water sources used for drinking water needs. There were four samples taken, namely I. water source in the pipe, II. water source outside pipe one, III. water source outside pipe two, IV. source of water flowing in the ditch. This research is a quantitative descriptive, while the data were analyzed using the Scoring Strunges method. Based on the results of laboratory scale tests, the results obtained include three parameters. Microbiological parameters of the physical parameters of the chemical parameters. The results of the water quality test on the water sample can be said to meet the requirements as clean water and dringking water. The things that affect the quality of drinking water include: color content, kesadahan total, mangan, pH, and organic substances.